TERRESTRIAL IMPACT MELT ROCKS AND GLASSES - Dressler B.O.; Reimold W.U. (My University, 2001)
The effects of meteorite and comet impact on Earth are rock brecciation, the formation of shock metamorphic features, rock melting, and the formation of impact structures, i.e. simple craters, complex craters, and multi-ring basins. Large events, such as the 65-Ma Chicxulub impact, are believed to have had catastrophic environmental effects that profoundly influenced the development of life on Earth.In this review, an attempt is made to summarize some of the voluminous literature on impact melting, one important aspect of planetary impact, provide some comments on this process, and to make suggestions for future research. The products of impact melting are glasses, impact melt rocks, and pseudotachylites. Our treatise deals mainly with the geological setting, petrography, and major-element chemistry of melt rocks and glasses.Impact glasses, in several petrographic aspects, are similar to volcanic glasses, but they are associated with shock metamorphosed mineral and rock fragments and, in places, with siderophile element anomalies suggestive of meteoritic contamination. They are found in allogenic breccia deposits within (fall-back ‘suevite’) and outside (fall-out ‘suevite’) impact craters and, as spherules, in distal ejecta. Large events, such as the K/T boundary Chicxulub impact, are responsible for the formation of worldwide ejecta horizons which are associated with siderophile element anomalies and shock metamorphosed mineral and rock debris. Impact glasses have a bulk chemical composition that is homogeneous but exemptions to this rule are common. On a microscopic scale, however, impact glasses are commonly strikingly heterogeneous.Tektites are glasses ejected from craters over large distances. They are characterized by very low water and volatile contents and element abundances and ratios that are evidence that tektites formed by melting of upper crustal, sedimentary rocks. Four tektite strewn-fields are known, three of which can be tied to specific impact craters.Impact melt rocks form sheets, lenses, and dike-like bodies within or beneath allogenic fallback breccia deposits in the impact crater and possibly on crater terraces and flanks. Dikes of impact melt rocks also intrude the rocks of the crater floor. They commonly contain shock metamorphosed target rock and mineral fragments in various stages of assimilation and are glassy or fine- to coarse-grained. Chemically, they are strikingly homogeneous, but as with impact glasses, exemptions to this rule do exist. Large and thick melt bodies, such as the Sudbury Igneous Complex (SIC), are differentiated or may represent a combination of impact melt rocks sensu-strictu and impact-triggered, deep-crustal melts.A concerted, multidisciplinary approach to future research on impact melting and on other aspects of meteorite and comet impact is advocated. Impact models are models only and uncritical reliance on their validity will not lead to a better understanding of impact processes—especially of melting, excavation, and deposition of allogenic breccias and the spatial position of breccias in relation to sheets and lenses of melt rocks within the crater. Impact-triggered pressure-release melting of target rocks beneath the excavation cavity may be responsible for the existence of melt rocks beneath the impact melt rocks sensu-strictu. This controversial idea needs to be tested by a re-evaluation of existing data and models, be they based on field or laboratory research. Only a relatively small number of terrestrial impact structures has been investigated in sufficient detail as it relates to geological and geophysical mapping.In this review, we summarize observations made on impact melt rocks and impact glasses in a number of North American (Brent, Haughton, Manicouagan, New Quebec, Sudbury, Wanapitei, all in Canada), Asian (Popigai, Russia; Zhamanshin, Kazakhstan), two South African structures (Morokweng and Vredefort), the Henbury crater field of Australia, and one European crater (Ries, Germany). Our tables listing major-element chemical compositions of impact glasses and melt rocks, however, include also data from structures not dealt with in further detail.